Beware of digital footprints: Wise social media usage for parents of early childhood students - Intan Putri Cahyani; Vinta Sevilla; Ruth Mariana Bunga Wadu (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
The COVID-19 pandemic has had a real impact on people's consumption patterns of social media which has increased by up to 40%. On the other hand, the use of social media leaves a digital footprint that cannot be erased. The students' parents of PAUD Soka Indah are the millennial generation who are very connected to their gadgets. Another problem is the lack of knowledge about the dangers of digital footprints as part of uncontrolled online activities and ignorance about the importance of managing digital privacy. Through the Information Communication and Education (IEC) Program, with the central theme of Wise social media, the team focused on the importance of being aware of digital footprints and how to ideally manage communication privacy in cyberspace. This Program uses the Participatory Rural Appraisal Model and aims to build awareness and understanding of being aware of digital footprints and the importance of managing privacy on social media. Previously, most participants were unfamiliar with digital footprints and rarely even paid attention to the terms and conditions of applications or social media. In addition, participants uploaded personal data several times on social media. After the team carried out the IEC program, the post-test results showed that all participants could explain the elements of digital footprints and distinguish between active and passive digital footprint categories. The following significant result is the follow-up on managing communication privacy on social media.